Disparate Effects of Disruptive Events on Children - Florencia Torche; Jason M. Fletcher; Jennie E. Brand (2024)
Disruptive events such as economic recessions, natural disasters, job loss, and divorce are highly prevalent among American families.These events can have a longlasting impact when experienced during childhood, potentially altering children's academic achievement, socioemotional wellbeing, health and development, and later life socioeconomic attainment.While much research has considered the overall impact of disruptive events on children's lives, the consequences of disruption also vary across groups.The same disruptive event may have profound negative consequences for some groups, minor or no impact for others, and even present a generative or positive turning point for other groups.This special issue focuses on the disparate consequences of disruptive events on children.We consider theoretical approaches accounting for effect heterogeneity and methodological challenges in identifying unequal impacts.We also review an emerging multidisciplinary literature accounting for variation in the impact of disruption across several widely studied domains that impact children's life chances, including economic, household, educational, health, and environmental events.